2019
DOI: 10.3390/md17060362
|View full text |Cite
|
Sign up to set email alerts
|

C-Phycocyanin Suppresses the In Vitro Proliferation and Migration of Non-Small-Cell Lung Cancer Cells through Reduction of RIPK1/NF-κB Activity

Abstract: Phycocyanin, derived from Spirulina platensis, is a type of natural antineoplastic marine protein. It is known that phycocyanin exerts anticancer effects on non-small-cell lung cancer (NSCLC) cells, but its underlying mechanism has not been elucidated. Herein, the antitumor function and regulatory mechanism of phycocyanin were investigated in three NSCLC cell lines for the first time: H358, H1650, and LTEP-a2. Cell phenotype experiments suggested that phycocyanin could suppress the survival rate, proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Recent anti-cancer studies of PC revealed a significant inhibitory effect on the growth of cancer cells in a time- and dose-dependent manner. Multiple mechanisms have been found, including the induction of apoptosis, cell cycle arrest, inhibition of DNA replication and the generation of reactive oxygen species (ROS) [ 32 , 36 , 37 , 38 ]. While apoptosis was significantly increased in cancerous cells, PC had a considerably lower toxicity on cells from healthy tissues, which makes it an appropriate candidate for chemotherapeutic applications [ 35 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent anti-cancer studies of PC revealed a significant inhibitory effect on the growth of cancer cells in a time- and dose-dependent manner. Multiple mechanisms have been found, including the induction of apoptosis, cell cycle arrest, inhibition of DNA replication and the generation of reactive oxygen species (ROS) [ 32 , 36 , 37 , 38 ]. While apoptosis was significantly increased in cancerous cells, PC had a considerably lower toxicity on cells from healthy tissues, which makes it an appropriate candidate for chemotherapeutic applications [ 35 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that phycocyanin can inhibit the proliferation, cause cell cycle arrest and induce apoptosis of NSCLC cells [ 34 , 35 ]. Previously, our team had discovered that phycocyanin exerted anti-proliferative functions through reducing receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and toll/interleukin 1 receptor domain-containing adaptor (TIRAP), two mediated proteins in multiple NSCLC cells, revealing the potential anticancer mechanism of phycocyanin in NSCLC [ 36 , 37 ]. Here, IRS-1, a key regulatory protein of phycocyanin, was investigated to participate in the growth and migration processes of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the fact that chemotherapeutic drugs employed for treatment of cancer are associated with several adverse side effects and short effective halflives in vivo. Indeed, natural products isolated from cyanobacteria are known for their potent anti-cancer activity [10,12,36]. Phycocyanin is a natural biologically active agent that is isolated and purified from various microalgae and seaweeds [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed to the role of C-PC as an antioxidant, anti-cancer, neuroprotective, immunomodulatory, anti-inflammatory agent, as well as a non-toxic photosensitizer in tumour treatment [5][6][7]. The importance of pure C-PC resides in its anti-proliferative and pro-apoptotic effects on different types of cancer cell lines [8][9][10][11], where there are no recorded side effects on normal cells [5,12]. For this reason, the purity of C-PC is considered the main challenge among researchers [3,13].…”
Section: Introductionmentioning
confidence: 99%